Broadband achromatic metalenses - Chin, Darren Yao Lim (Nanyang Technological University, 2024)
Lenses capable of achromatic focusing are essential for broadband operations ranging from spectroscopy to hyperspectral imaging systems. Recent meta-optics studies have ushered in a new generation of lenses in the form of broadband achromatic metalenses. These devices can overcome chromatic aberration with a single metalens as compared to the thick cascade of lenses normally required in conventional imaging systems. While achromatic metalenses have been widely demonstrated for visible wavelengths, similar works in the Terahertz regime have been limited. Even so, existing design processes often prioritize achieving constant focal length and lacks control over the point spread function (PSF) and depth of focus (DOF) responses by the lens across its bandwidth. As the field of metamaterials have expanded to include multi-frequency applications, inverse design for metasurfaces have recently garnered much traction in the scientific community for its potential to generate the most optimal shape and structures; which are difficult to obtain based off intuition alone. In this research, an evolutionary heuristic called Genetic Algorithm (GA) is utilized to computationally model a metalens operating at a bandwidth of 0.25 to 0.5 THz with a numerical aperture of 0.366. In addition to controlled focal point, the metalens also shows outstanding resolution capability as a full width half maximum (FWHM) as low as 1.25λ is achieved.